2014
DOI: 10.3329/bmrcb.v39i3.20310
|View full text |Cite
|
Sign up to set email alerts
|

An open randomized controlled trial to compare the efficacy of two fixed dose combinations of artemesinin based combinations for uncomplicated falciparum malaria in Bangladesh

Abstract: National Malaria Control Program (NMCP) of Bangladesh has introduced Artemisinin Based Combination (ACT), Coartem (R) (Artemether-Lumefantrine (AL), fixed dose combination, in the confirmed cases of uncomplicated P. falciparum malaria since 2004. Despite the reduction of mortality due to malaria, the development and spread of anti-malarial drug resistance wordwide posing a threat to the health services and will make it difficult to control malaria in Bangladesh in future. We need to have an alternative to Coar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…Reassuringly, in patients with P . falciparum the parasite clearance half-life was 2.75 hours with a median PCT of 22.0 hours, values well within the range expected of fully sensitive parasites and similar to earlier reports from this region [ 14 , 32 , 36 , 37 , 9 ].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Reassuringly, in patients with P . falciparum the parasite clearance half-life was 2.75 hours with a median PCT of 22.0 hours, values well within the range expected of fully sensitive parasites and similar to earlier reports from this region [ 14 , 32 , 36 , 37 , 9 ].…”
Section: Discussionsupporting
confidence: 89%
“…vivax parasitaemia within 12 hours and all by 36 hours. A recent meta–analysis found that clearance of parasites in >95% of participants within 48 hours (as was seen in the current study) is highly indicative of CQ sensitivity [ 14 ].…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…20 In Bangladesh, clinical trials of ACTs, for example, AL, artesunate-mefloquine, artesunate-amodiaquine, and artesunate-azithromycin, have shown excellent efficacy, with rapid parasite clearance and high rates of treatment success. [21][22][23][24][25] Although AL is the mandated treatment for uncomplicated malaria, CQ remains available as an over-thecounter medication for self-treatment of malaria, as well as for vivax malaria treatment in some parts of the country. 26,27 Several drug resistance mechanisms have been reported in P. falciparum; CQ resistance (CQR) has been linked to the mutation in the P. falciparum chloroquine resistance transporter gene (pfcrt) at codon 76.…”
Section: Introductionmentioning
confidence: 99%